Pemetaan Jasa Ekosistem Mangrove pada Wilayah Rehabilitasi di Pesisir Sayung, Kabupaten Demak - Setyo Handayani; Luky Adrianto; Dietriech Geoffrey Bengen; I Wayan Nurjaya; Yusli Wardiatno (Jurnal Ilmu Pertanian Indonesia, 2020)
The mangrove ecosystems on the coast of Sayung Sub-District provide huge benefits to the community. However, this region experienced a very severe coastal erosion during the last few decades. Also, information about mangrove ecosystem services is still very limited in this region. The purpose of this study, therefore, was to map the balance of mangrove ecosystem services on the coast of Sayung Sub-District, Demak District. Data were collected from three coastal villages, namely Bedono, Timbulsloko, and Surodadi, through in-depth interviews, questionnaires, and field observations. The data analysis was carried out using the Burkhard model approach, which involved an ecosystem service matrix, made up of a matrix of capacity, demand, and availability. The results showed that in all components of provisioning service, there was a surplus of availability. In regulating services, there were low surpluses in the components of carbon sequestration and water bioremediation services, while low deficits were found in the service components of reduce wave and current damage, and protecting from sea water intrusion. Then, in cultural services, the two components, shelter for rest area and recreation, experienced a surplus of availability. Mangrove rehabilitation needs to be continued to increase mangrove cover, given the availability of regulating services on components related to erosion prevention in the balace sheet tends to be deficit. Keywords: Burkhard Model, ecosystem services, mangrove ecosystem, Sayung coastal